Integrasi Biosistem Peternakan Sapi Potong, Biogas, dan Sayur di Lahan Pasang Surut Tanjung Jabung Timur Provinsi Jambi - Santoso, A. J.; Fuah, A. M.; Salundik, Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The utilization of tidal land as agricultural land has been carried out in line with the reduction of agricultural land in Indonesia. Research was conducted at Simpang Village, Tanjung Jabung Timur, Jambi province as one of the areas in Indonesia where tidal land is used for agricultural purpose. In the research site found that, in general, farming and animal husbandry are done in a separated system. The agricultural integrated system would provide more optimal results called Integrated biosystem. The Biosystem includes animal husbandry, biogas utilization and vegetable cultivation. The aim of this study is to develop and apply the applicable integrated biosystem to improve production, efficiency and farmer’s revenue. The results showed that by applying integrated biosystems, farmers will gain more benefits in the form of biogas utilization for daily cooking, and  the utilization of sludge as the byproduct of biogas for organic fertilizer  which is meet  the SNI criteria (19- 7030-2007). The utilization of sludge on vegetable crops statistically significant (P <0.05) to enhance the growth of stems, leaves and fresh weight Ipomea reptana Poir compared with inorganic fertilizers (Phonska) and control. Furthermore, The analysis of economic efficiency for a one-year calculation shows that integrated biosystem provides net profit as much as Rp. 22,578,700(NPV=61,801,516; B/C Ratio=2,77; Payback period=1,69), while the otherwise only produce as much as Rp 15,000,600(NPV=45,521,689; B/C Ratio=2,89; Payback period=1,62).